Visitantes florais e polinização da castanha-do-brasil (Bertholletia excelsa h. & b.) em cultivo na amazônia central - Cavalcante, Marcelo Casimiro (2008)
The research was carried out in Aruanã farm, county of Itacoatiara, in the state of Amazonas, Brazil, in an area of 3,600 ha cultivated Brazil nut tree (Bertholletia excelsa). Data were collected from October to December 2007, to investigate floral visitors and the pollination of grafted Brazil nut trees cultivated in Central Amazon Forest, aiming to maximize the crop productivity. Floral biology and pollination requirements of this crop were assessed as well as richness, diversity and abundance of floral visitors in relation to the flowering phase of the trees (5, 25 and 50%); foraging behavior of bees visiting the flowers, initial fruit set and number of seeds set per fruit in hand and bagging pollination experiments (open pollination, restricted pollination, hand cross-pollination, hand self-pollination and hand geitonogamy). Results showed that 19 bee species, belonging to three Families, visited the flowers all-day long collecting nectar and pollen. Richness, diversity and abundance varied according to the blooming stages, showing increments to the former two and decrease in bee abundance per tree as blooming progressed. The most abundant and frequent species in the area during the whole blooming period were Xylocopa frontalis (63%) and Eulaema mocsaryi (12%). Natural pollination levels found showed to be lower than the crop’s potential observed by hand pollination. The Brazil nut tree allows geitonogamy (3.85%) in initial fruit set, but its level is significantly lower (p>0,01) than that of hand cross-pollination (19.33%), which needs biotic pollinators, in this case large-sized bees, to accomplish successful pollination. The number of viable seeds varied significantly (p>0.05) among treatments showing that open pollination and hand cross-pollination produced similar results between them, but greater than geitonogamy. The forging behavior of E. mocsaryi and X. frontalis led to the conclusion that they are the main pollinators of ertholletia excelsa under cultivation in that area. Richness, diversity and abundance of flora visitors and potential pollinators can be related to the surrounding forest which provides adequate environment to keep pollinators in periods of the year when the crop is not blooming